2015
DOI: 10.1177/0883073815575366
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase and Catalase Genotypes in Pediatric Migraine Patients

Abstract: This study compared superoxide dismutase (SOD) and catalase (CAT) alleles in 97 consecutive children and adolescents with migraine to 96 healthy children and adolescents. Isolated genomic DNA was used as a template for SOD1 (35 A/C), SOD2 16 C/T, and CAT2 [(-262 C/T) and (-21 A/T)] allele genotyping. The SOD2 16 C/T genotype and C allele frequency differed significantly between controls and migraine (P = .047; P = .038). CAT -21 AA genotype and A allele frequency were significantly higher in both migraine with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“… 22 , 26 By contrast, children with migraine were found to have higher CAT levels than healthy controls. 27 Several studies have demonstrated that inadequate antioxidant defense systems are associated with different types of headache. 22 , 28 30 Eren et al 6 reported that the TAS values of migraine patients and controls were similar, and another recent study of patients with migraine also showed similar TAS in migraineurs and controls.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 26 By contrast, children with migraine were found to have higher CAT levels than healthy controls. 27 Several studies have demonstrated that inadequate antioxidant defense systems are associated with different types of headache. 22 , 28 30 Eren et al 6 reported that the TAS values of migraine patients and controls were similar, and another recent study of patients with migraine also showed similar TAS in migraineurs and controls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a polymorphism (the rs4880 TT (Val/Val) genotype) in the gene that enco des superoxide dismutase 2 (SOD2), a crucial enzyme in the clearance of mitochondrial ROS, has been associated with unilateral cranial autonomic symptoms in patients with migraine with aura 133 . In paediatric patients with migraine, the C-T genotype and C allele at position 16 of SOD2 and the A-A genotype and A allele at position 21 of CAT (which encodes catalase) were more frequent among patients with migraine with or without aura than among healthy controls 134 . Both enzymes act in concert to reduce ROS accumu lation, and the polymorphisms reported in this study are thought be associated with reduced transcriptional and/or enzyme activity, meaning people with migraine are more vulnerable to oxidative stress.…”
Section: Non-mitochondrial Genesmentioning
confidence: 96%
“…Three genetic polymorphisms have been reported in the promoter region of the CAT named A-21T (rs7943316), C-262T (rs1001179) and C-844T (rs769214) [2][3][4]. Previous studies have shown that CAT polymorphisms were associated with the risks of several multifactorial diseases [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%